A longitudinal study of creatine kinase and creatinine levels in Duchenne muscular dystrophy. Issue 2 (5th December 2022) - Zygmunt, Alexander M.; Wong, Brenda L.; Horn, Paul S.; Lambert, Joshua; Bange, Jean E.; Rybalsky, Irina; Chouteau, Wendy; Tian, Cuixia
Abstract: Introduction/Aims: Management of Duchenne muscular dystrophy (DMD) has entered an era featuring novel treatments. Trackable noninvasive biomarkers could improve disease progression monitoring and drug effect detection. Our aim in this study was to measure changes in selected noninvasive biomarkers and assess their relationship to age and motor function. Methods: We retrospectively studied 555 patients with DMD who had at least 12 months of treatment of glucocorticoids and were not enrolled in trials of potential disease‐modifying therapies. We extracted biomarker data of serum creatine kinase (CK), serum creatinine (Cr), urine Cr, and urine Cr/urine osmolality (osm), as well as functional data for age at loss of ambulation and Functional Motor Scale (FMS) values from patients' clinical records. Data were analyzed using linear mixed‐model analyses. Results: CK, serum Cr, urine Cr, and urine Cr/urine osm all decreased with declining motor function. CK consistently decreased and FMS score consistently worsened with age without clear inflection points. There was an increased odds ratio for LOA with lower values of CK, serum Cr, urine Cr, and urine Cr/urine osm, most notably for urine Cr. Discussion: Although individual biomarker values are challenging to directly apply clinically, our study has demonstrated that trends over time may complement functional measures in the assessment of individuals with DMD. Future studies could elucidate predictive utility of these biomarkers in assessing motor function changes in DMD.